223k views
2 votes
If you were to use the substitution method to solve the following system, choose the new

equation after the expression equivalent to y from the second equation is substituted into
the first equation.
2x - 7y = 4
3x + y = -17


Pls answer

User Lipenco
by
6.0k points

1 Answer

4 votes

Answer:

23x = -115

Explanation:

In the substitution method, you must solve for 1 variable in 1 equation to replace it in the other equation. For the system:

2x - 7y = 4

3x + y = -17

Solving for y in the second equation:

y = -17 - 3x

Replacing y in the first equation:

2x - 7(-17 - 3x) = 4

2x + 119 + 21x = 4

23x = -115

This is the new equation after use the substitution method.

User Alexander Yatsenko
by
6.3k points